Wings on concealed corpse: the forensic importance of scuttle flies (Diptera: Phoridae) - Guo, Yali; Luo, Yifei; Ma, Yuting; Luciano, Afito; Huang, Jingjing; Li, Ye; Wang, Shiwen; Niu, Yuequn; Li, Zhou; Cai, Jifeng; Meng, Fanming (Frontiers in Insect Science, 2026)
Forensic entomology focuses on insects associated with decomposing remains to provide clues for forensic investigations. Among those insects, scuttle flies are uniquely capable of colonizing enclosed spaces and underground burial sites where other insects cannot access, often serving as the sole entomological “witnesses” to provide crucial evidence in forensic practice. This review highlights the forensic significance of scuttle flies, including the biological characters, diversity and behaviors of scuttle flies from forensic aspects based on reported cases. We investigate the biological and environmental factors influencing their utility in forensic investigation, and scuttle fly species commonly found on corpses were also summarized. Additionally, suggestions on future research directions of scuttle flies and how their biological characteristics can enhance their application in forensic entomology are also provided.